2013
DOI: 10.4034/rbcs.2013.17.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Núcleo de Apoio à Saúde da Família: Refletindo sobre as Acepções Emergentes da Prática

Abstract: RESUMO Objetivo: Analisar as práticas profissionais das equipes dos Núcleos de Apoio à Saúde da Família (NASF) dos municípios de Campina Grande e João Pessoa, em consonância com os modelos de apoio matricial identificados. Metodologia: Realizou-se observação não-participante junto aos profissionais do NASF de Campina Grande e João Pessoa, em um total de 480 horas, em que puderam ser observadas capacitações promovidas pela Secretaria Estadual de Saúde e Ministério da Saúde para as equipes NASF, reuniões entre e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
15

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 2 publications
0
5
0
15
Order By: Relevance
“…However, neither the Notebook of Primary Care No 39 or Ordinance No. 154, which define the criteria of assistance in FHSC and FHS, distinguish what the "specific cases" would be [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, neither the Notebook of Primary Care No 39 or Ordinance No. 154, which define the criteria of assistance in FHSC and FHS, distinguish what the "specific cases" would be [12].…”
Section: Discussionmentioning
confidence: 99%
“…One of the disadvantages of FHSC teams is that the professionals often return to performing only outpatient care, which results in the lack of integration with the professionals from FHS teams and other sectors that could come to ensure the targeting of intersectional actions [13] In Campina Grande, State of Paraíba, Sampaio et al [12] found that there is a predominance of care In João Pessoa, State of Paraiba, assistance activities were not observed over the research period, nor were technical and pedagogical action developed by FHSC teams, but only several action of managerial nature. However, it was identified in the register form for supporters of that municipality that there are some indications to the execution of activities such as: conducting individual care, no specific individual consultation, pre-consultation, vaccination, dressings, injectable medications, cytological examination, exchange of catheters, blood glucose checking, anthropometric measurements and checking of vital signs [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tal situação pode apontar para o caráter clínico-assistencial, 9 predominante do NASF, bem como para a possível transferência do cuidado para esta equipe, que foge da lógica do apoio matricial. 3 No âmbito do planejamento de ações conjuntas, constata-se que 75,9% das EqAB articularam ações conjuntas com o NASF desde o momento em que este começou suas atividades na unidade, o que reflete um fator favorável à integração das equipes.…”
Section: Resumo Dos Principais Achados Do Estudounclassified